Políticas econômicas anticíclicas e seus efeitos regionais e setoriais utilizando um modelo de equilíbrio geral computável inter-regional - Nunes, Marivia de Aguiar (2015)
The aim of this research was estimate the effects of indirect and direct taxes. Therefore, the option was the construction of two simulations - the first assesses the effects of consumption stimulus measures implemented by the Brazilian federal government in 2008/2009 in countercyclical actions, while the second proposes an alternative policy to that established by the Ministry of Finance, namely, a reduction in the rate of direct taxes, which would tend to increase disposable income and, because of that, the consumer. Also in this last exercise, it is assumed that government spending remain unchanged. The methodology applied is a Computable General Equilibrium model (CGE) adapted to the Brazilian economy, the TERMBR (The Enormous Regional Model).